2012
DOI: 10.1098/rstb.2012.0010
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases display minimal interpositional dependence on substrate sequence: potential implications for the evolution of signalling networks

Abstract: Characterization of in vitro substrates of protein kinases by peptide library screening provides a wealth of information on the substrate specificity of kinases for amino acids at particular positions relative to the site of phosphorylation, but provides no information concerning interdependence among positions. High-throughput techniques have recently made it feasible to identify large numbers of in vivo kinase substrates. We used data from experiments on the kinases ATM/ATR and CDK1, and curated CK2 substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Additionally, the sequence surrounding the phosphorylation site also affects substrate positioning, and can therefore affect phospho-acceptor site specificity. As an example of this interdependence, we have previously noted that the preference of the kinases ATM/ATR for phosphorylating serine-glutamine versus threonine-glutamine motifs appears to depend on the residues found at other positions in the motif (Joughin et al, 2012). A similar observation of interdependence between phospho-acceptor residue identity and specific amino acids in other positions within the motif has been shown for the dual-specificity kinase CK2 (Marin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sequence surrounding the phosphorylation site also affects substrate positioning, and can therefore affect phospho-acceptor site specificity. As an example of this interdependence, we have previously noted that the preference of the kinases ATM/ATR for phosphorylating serine-glutamine versus threonine-glutamine motifs appears to depend on the residues found at other positions in the motif (Joughin et al, 2012). A similar observation of interdependence between phospho-acceptor residue identity and specific amino acids in other positions within the motif has been shown for the dual-specificity kinase CK2 (Marin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Computational analyses have suggested that kinases display little inter-positional dependence in their primary peptide specificity and that each substrate peptide amino acid interacts with the kinase active site more or less independently ( Joughin et al, 2012 ). Our observation that +1 specificity is dependent on the identity of the phosphoacceptor represents an exception to this model.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, CK2 has more than one active site on substrates, and overall about 75% of the active sites match the CK2 motif S/T-X-X-D/E (30). Within the VP8 sequence, 10 threonines and 19 serines match the motif.…”
Section: Discussionmentioning
confidence: 99%